Plasma fibrinogen as a potential biomarker of cognitive impairment after acute ischemic stroke - Chunxiao Wei; Weijie Zhai; Panpan Zhao; Li Sun (Scientific Reports)
Abstract Fibrinogen (FBG) has been discovered to be associated with cognitive impairment (CI) and dementia. However, the exact correlation between FBG levels and CI after acute ischemic stroke (AIS) remains uncertain. Plasma FBG levels were measured in 398 patients with AIS who underwent comprehensive neuropsychological evaluation. To assess the correlation of FBG with global cognitive function, physical status, anxiety, depression, and psychiatric symptoms. Multifactorial logistic regression was used to analyze risk factors for CI. Constructed and plotted a nomogram graph to visualize the CI prediction model. The model was further evaluated for discrimination, calibration, and clinical utility. The results indicate that plasma FBG levels are significantly elevated in patients with CI compared to those with non-cognitive impairment (NCI). Analysis of the overall population reveals that elevated FBG levels are correlated with both reduced cognitive function and decreased activity status. After adjusting for other influencing factors, high FBG levels were identified as a risk factor for the incidence of CI. We developed an intuitive and valid predictive model for CI, demonstrating its suitability for clinical application. In conclusion, our study demonstrates that plasma FBG serves as a potential biomarker of CI following AIS, offering a novel perspective for the identification of CI.